Pengaruh Lingkungan Kerja Terhadap Kinerja Guru Pendidikan Agama Islam di Mts Negeri Sentajo Filial Singingi Kecamatan Singingi Kabupaten Kuantan Singingi - Rifa Elfita; Zulhaini Zulhaini; Ikrima Mailani (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2019)
Abstract: The problem in this study is the low performance of teachers due to lack of facilities (physical and non-physical environment or learning support infrastructure owned by MTs Negeri Sentajo Filial Singingi The main objective of this research is to find out the Work Environment at Sentajo Filial Singingi MTs Negeri Singingi District, Kuantan Singingi Regency. To find out the performance of PAI Teachers at the Sentajo Filial Singingi MTs Negeri Singingi Subdistrict, Kuantan Singingi Regency and to find out the effect of the work environment on PAI Teacher Performance at Sentajo MTs Negeri Filing Singingi, Singingi District, Kuantan Singingi Regency Based on the results of data collection by means of observation, interviews, questionnaires and documentation, the data were analyzed using simple Linear Regression formula and SPSS windows 20.0 so it can be concluded that: The working environment at Sentajo MTs Negeri Singingi District Singingi District, Kuantan Singingi Regency is which is quite good, namely 68%. The performance of Islamic Education teachers at the Sentajo Filial Singingi MTs Negeri Singingi Subdistrict, Kuantan Singingi Regency is quite high at 58% There is the Effect of Non Physical Work Environment on the Performance of Islamic Education Teachers in Sentajo Filial Singingi MTs Negeri Singingi Subdistrict, Kuantan Singingi Regency, which is known as the value of determination coefficient (R Squere) of 0.791 (is the calculation of correlation coefficient, or 0.843 x 0.843 = 0.710649) . The magnitude of the determination coefficient (R square) 0.710 numbers implies that the Work Environment has a strong influence on the performance of Islamic Education teachers. Keywords: Work Environment, Teacher Performance in Islamic Education